Virtual Service-Learning in Higher Education. A Theoretical Framework for Enhancing its Development - García-Gutiérrez, Juan; Ruiz-Corbella, Marta; Manjarrés Riesco, Ángeles (Frontiers in Education, 2021)
The last decade have witnessed the unprecedented development of information and communication technologies. This has, in turn, enabled the growth and development of other sectors, such as, for example, that of distance and on-line learning. In this context of technological expansion in education it is appropriate to reflect pedagogically about technological resources and their educational purpose. That is, how to deploy the available technological resources and media in a fashion consistent with the desired educational objectives and aims. Virtual Service-Learning has emerged as a particular modality of this methodology that combines and reinforces two elements: technology applied to education and service as a pedagogic tool. This format then, reveals itself as an appropriate methodology through which to channel both technical and pedagogic innovation. In this work and, taking as reference a study focusing on two virtual Service-Learning projects, we will address the construction of a theoretical framework that will allow us to understand and improve the development of these practices through this pedagogic modality.